ANALISIS KINERJA AGRIBISNIS PADI ORGANIK PETANI BINAAN JAMTANI DI KABUPATEN PANGANDARAN - Mai Fernando Nainggolan; Iwan Setiawan; Trisna Insan Noor; Tualar Simarmata; Kustiwa Adinata; Silke Stoeber (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Although organic farming, one of which is organic rice, many benefits and positive effects have been mentioned, if we observe the development, it has not yet reached its maximum production. The purpose of this study was to describe the performance of the agribusiness subsystem in the development of organic rice agribusiness for farmers. This research was carried out in several farmer groups assisted by JAMTANI spread across the villages of Cimurutu, Paledah, and Padaherang who are organic rice farmers in the area. The sampling technique used in this research is using cluster random sampling technique with the number of respondents as many as 120 farmers who are fostered by JAMTANI. Performance was analyzed using descriptive statistics. Research results Based on the agribusiness system approach consisting of input supply subsystems, cultivation, harvest and postharvest handling, marketing and support, it shows that the performance of organic rice agribusiness on JAMTANI partner farmers in Pangandaran district obtained adequate performance. Changes in production when viewed from the number of farmers, as many as 120 people have experienced changes in the amount of production.